(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
It is known from history that in all Eastern countries, a person, his dignity, rights, honor, feelings have been glorified as the highest value for centuries, and this tradition continues to this day. In particular, in the land where we live, a number of works have been written since ancient times, guaranteeing the rights of people and glorifying their prosperous lifestyle. In particular, we can clearly see that the ideas of tolerance played a major role in the work of Abu Nasr Al-Farabi, one of the famous thinkers of the East, who lived and worked in the late 9th and first half of the 10th centuries.